A clinical approach to diagnose patients with localized telangiectasia. (6th May 2015) - Gupta, Ruchi; Gautam, Ram Krishan; Bhardwaj, Minakshi; Chauhan, Amrita
Abstract Telangiectasia, or dilated blood vessels, may represent a benign condition or a marker of a much more serious internal or cutaneous malignancy (e.g. mycosis fungoides). They can be generalized or localized in distribution. 'Localized telangiectasia? can be macular or papular. Macular ones can be further divided into two major categories: primary and secondary. They can occur on their own (primary), after skin injury (e.g. sun damage, post‐radiation therapy, after prolonged topical steroid application), or may arise due to an underlying condition (secondary). While telangiectases can spring from a multitude of possible causes, the location of the lesions, in combination with a careful history and exmination, often helps in elucidating the correct diagnosis. A patient with localized telangiectasia as a manifestation of malignancy may be difficult to diagnose, however the diagnosis is one of exclusion, and a thorough evaluation should be performed before diagnosing this condition. This article reviews possible conditions to consider in these patients and suggests an approach to their evaluation.